A strategy for achieving manufacturing statistical process control within a highly complex aerospace environment - Veira, Adryan; Khan, Khurshid; Farrell, Ian (Cranfield University Press, 2013)
This paper presents a strategy to achieve process control and overcome the previously mentioned industry constraints by changing the company focus to the process as opposed to the product. The strategy strives to achieve process control by identifying and controlling the process parameters that influence process capability followed by the implementation of a process control framework that marries statistical methods with lean business process and change management principles. The reliability of the proposed strategy is appraised using case study methodology in a state of the art manufacturing facility on Multi-axis CNC machine tools.
Keywords: Process Control; Process Capability; Multi-axis Machine tools